Can creative role models prime creativity in soccer players?. (July 2018) - Furley, Philip; Memmert, Daniel
Abstract: Objectives: The goal of the present study was to test if priming soccer players with certain players that are known for extraordinary creativity can lead to enhanced creativity in a computer-based decision-making task. Design: Between-subject experimental designs were implemented. Method: Using a sequential priming procedure amateur soccer players were primed with either creative (Lionel Messi; Thiago Alcántara) or uncreative soccer players (Per Mertesacker; John Terry) and subsequently performed a soccer decision-making task. The priming stimuli were changed from Experiment 1 ( N = 60) to Experiment 2 ( N = 60), and the priming procedure was changed in Experiment 3 ( N = 60). Results: All three experiments revealed large ( d = 0.91 in Experiment 1 and d = 1.75 in Experiment 2) to moderate effects (Experiment 3; d = 0.59) of priming on creative decision making in soccer. Conclusion: Domain-specific creative thinking can be influenced by priming amateur soccer players with soccer stars that are known to differ in terms of creativity. Both the practical implications of the findings for soccer and the methodological implications for future priming research in sport are critically discussed. Highlights: Soccer players' creative thinking can be primed by creative soccer stars. Non-creative primes can decrease creativity in soccer. The priming effect was replicated across different primes and procedures. Moderators influence the occurrence and strength of priming effects.